The Influence of Organizational Culture and Organizational Commitment on Employee Performance at the Ministry of Manpower of the Republic of Indonesia - E. Nurzaman AM (Budapest International Research and Critics University, 2020)
This study aims to determine the effect of organizational culture and organizational commitment on employee performance at the Ministry of Manpower of the Republic of Indonesia. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study that organizational culture has a significant effect on employee performance by 38.3%, hypothesis testing is obtained t count > t table or (7.757 > 1.985). Organizational commitment has a significant effect on employee performance by 41.7%, hypothesis testing is obtained t count > t table or (8.335 > 1.985). Organizational culture and organizational commitment simultaneously have a significant effect on employee performance with the regression equation Y = 9.612 + 0.326X1 + 0.442X2. Contribution of influence is 51.7%, hypothesis testing obtained F count> F table or (51.364> 2,700).